A Developmental and Life-Course Approach to Further Understanding of the Nature and Causes of Intimate Partner Violence and Femicide - Narvey, Chelsey S. (Journal of contemporary criminal justice, 2024)
The current paper explores the theoretical and empirical capacity of developmental and life-course criminology (DLC) to further our understanding of non-lethal intimate partner violence (IPV) and femicide. Drawing on Sampson and Laub’s age-graded theory and Moffitt’s dual taxonomy, the paper delves into empirical research that has identified and examined the overlap between general offending and IPV, highlighting how these DLC theoretical frameworks could provide insight into non-lethal IPV and femicide. We also outline the ways in which these DLC perspectives are challenged to fully address the gendered nature of IPV and less able to provide an empirical and theoretical understanding of the role of power and control by men over their women partners. We then place these frameworks within the global impact of the COVID-19 pandemic on gender-based violence, including femicide. While the COVID-19 lockdowns increased vulnerability to IPV and increased homicide in the United States, the expected rise in femicide did not materialize—at least within the United States, prompting questions about the extent to which existing criminological theories are able to provide a framework for these types of crime trends during unprecedented events. We examine the way non-lethal and lethal IPV are shaped by different factors as outlined in Moffitt’s dual taxonomy. The pandemic for example did not create increased psychopathy (i.e., affective and personality disorders) associated with the risk for femicide, but the COVID-19 pandemic and the subsequent lockdowns did create increased economic and family stressors, which placed many at-risk women and children in further social isolation, and reduced access to victim services. We conclude a need for further theoretical development surrounding femicide, integrating developmental and life-course perspectives, thereby emphasizing the need for refined frameworks to address the intricate dynamics of violence against women globally.